Faktor-Faktor yang Berhubungan dengan Implementasi Promosi Kesehatan Rumah Sakit - Mufid, Achmad; Sulaeman, Lalu; Sastrawan, Sastrawan (Journal of Telenursing (JOTING), 2023)
This study analyzes factors (superior support, commitment, resources, and communication) related to implementing Hospital Health Promotion (PKRS). The method used is quantitative with a cross-sectional analytical approach. The research results showed that there was a relationship between superior support (p=0.001), commitment (p=0.027), resources (p=0.000), and communication (p=0.022) on the implementation of Hospital Health Promotion (PKRS). In conclusion, the better the support from superiors, commitment of implementers, resources, and communication, the better the implementation of PKRS. Keywords: Supervisor Support, Commitment, Resources, Communication, Health Promotion